‘Wrong Price Tag’ at a Supermarket in the Focus of General Principles of Law - KOROLEV, Sergei Viktorovich; SHULZHENKO, Yuri Leonidovich; RUSAKOVA, Ekaterina Petrovna; BATYAEVA, Albina Ramazanovna; DUDIN, Mihail Nikolaevich (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018, 2018)
The article compares the German and Russian sales contract models by the example of civil cases illustrating the specifics of shopping at a supermarket. Analyzing the ratio of offer and acceptance, as well as the specifics of invitatio ad offerendum and the so-called public agreement, the authors capture the gaps of legal regulation for both models. Basing on the materials presented in this article, the authors consider it necessary to formulate the following main conclusions: legal uncertainties exist not only in the civil and economic transactions in Russia and Germany. The civil cases considered in this article were studied not only from the perspective of national legislation norms of Germany and Russia but also in the context of general principles of law, the reasonable person standard and the trust protection principle; the model of the sales contract adopted in the Russian law leaves the seller and the buyer in a stalemate when solving the problem of a wrong price tag at the supermarket checkout. Moreover, such model in the trend creates a complex legal and technical issue. On the contrary, the German law model of the sales contract unambiguously indicates the fact that it is impossible to recognize the wrong price tag as mandatory, as this contravenes with the freedom-of-contract doctrine; the dominant paradigm of legal positivism determines that legal value is given only to the principles clearly entrenched in the active legislation. In the absence of positive law standards, these gaps can be filled by applying the general principles of law recognized by the civilized nations.